Título Padrão - de Morais, Jáder Onofre (Arquivos de Ciências do Mar, 2018)
A separation of heavy minerais and the study of sediments under a binocular microscape have been carried out, as well as chemical and petrological analysis. All the results together with some reference papers have been riiscussed, in an attempt to ascertain the contribution made by the volcanic material, and whether they are more closely related to river transportation or other means of transport.